Preparation and characteristics of lauric acid-myristic acid-based ternary phase change materials for thermal storage. (August 2022) - He, Qian; Fei, Hua; Zhou, Jiahong; Du, Wenqing; Pan, Yucheng; Liang, Ximei
Abstract: Latent heat energy storage technology is an important measure in the field of energy conservation. In this work, lauric acid and myristic acid were used as binary matrix, two ternary phase change materials of lauric-myristic-palmitic acid and lauric-myristic-paraffin section were prepared by introducing palmitic acid and paraffin section. Two ternary eutectic phase diagrams were obtained by analyzing the binary system, the optimal quality proportions of lauric-myristic-palmitic acid and lauric-myristic-paraffin section were 59:26:15 and 51:28:21, respectively, the phase transition temperatures were 32.24 °C and 31.50 °C, the difference between the theoretical predicted temperature and the experimental results is 0.95 ℃ for lauric-myristic-palmitic acid, which is basically consistent with the theoretical values. The enthalpies were 160.41 J/g and 172.37 J/g for the two groups of ternary phase change materials, and the research indicated that they were physically mixed and had good thermal stability at working temperature. After 500 thermal cycles, lauric-myristic-palmitic acid exhibited better thermal reliability compared to lauric-myristic-paraffin section. The results show that both groups of ternary phase change materials have excellent thermal properties and can be used in engineering applications over a long period of time. Graphical Abstract: Lauric-myristic-palmitic acid and lauric-myristic-paraffin section phase change materials with good thermal properties and stable chemical properties were prepared by melt blending. ga1